Role of the PI 3-kinase signaling pathway in cell regulation and human disease - Cantley, Lew (Henry Stewart Talks, 2010)
Phosphoinositide 3-kinase (PI3K) signaling, Class Ia PI3K's and the mediation of growth factor signaling, The receptor tyrosine kinase signaling pathway, Loss-of-function mutations in tumor suppressors, Sporadic mutations, Drug targets, Regulation of metabolism by PI3K AKT signaling, Targets of the drug NVP BEZ235, Generation of mice with mutant PI3K p110a, How lung adenocarcinoma requires mutant PI3K, HIF-1alpha, Visualizing lung tumors using FDG PET, How mTOR inhibition does not reduce tumor volume, Will a PI3K inhibitor kill K-Ras driven tumors?, How AKT inhibition does not affect tumor size or activity, Effects of BEZ235 in K-Ras mutant tumors, How BEZ235 specifically kills PI3K driven tumors, The drug ARRY 886, How PI3K with MEK inhibitors eradicates K-Ras tumors, Blocking the PI3K and MAP Kinase pathways, Inhibition of S6 kinase in K-Ras tumors